1988
DOI: 10.1007/bf01968074
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase metabolites mediate increased airways resonsiveness to histamine after acute platelet activating factor exposure in the guinea-pig

Abstract: Platelet activating factor (Paf, 0.02 micrograms/kg, i.v. bolus) caused an acute increase in airways responsiveness to histamine in anaesthetized guinea-pigs prepared for recording airways resistance (RL) and dynamic compliance (Cdyn). Aspirin pretreatment (10 mg/kg, i.v.) attenuated the return of airways responsiveness to prechallenge levels. Pretreatment with the combined cyclooxygenase/lipoxygenase inhibitors BW 755C (20 mg/kg, i.v.) and ETYA (20 mg/kg, i.v.), or with the putative cysteinyl-containing leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This report also suggests that a mixture of drugs (PAF receptor antagonists, lipoxygenase pathway inhibitors and perhaps eicosanoid receptor antagonists) when they become available for clinical trials may prove to be synergistic in their actions since they may prevent several steps in a common series of events. This is supported by recent findings suggesting that PAF induced bronchial hyperreactivity in vivo in guinea pigs is inhibitable by lipoxygenase pathway inhibitors [36]. Thus, PAF may cause an activation of the lipoxygenase pathway of eicosanoid metabolism which leads to the production of eicosanoids with mucus secretagogue effects.…”
Section: Discussionsupporting
confidence: 61%
“…This report also suggests that a mixture of drugs (PAF receptor antagonists, lipoxygenase pathway inhibitors and perhaps eicosanoid receptor antagonists) when they become available for clinical trials may prove to be synergistic in their actions since they may prevent several steps in a common series of events. This is supported by recent findings suggesting that PAF induced bronchial hyperreactivity in vivo in guinea pigs is inhibitable by lipoxygenase pathway inhibitors [36]. Thus, PAF may cause an activation of the lipoxygenase pathway of eicosanoid metabolism which leads to the production of eicosanoids with mucus secretagogue effects.…”
Section: Discussionsupporting
confidence: 61%
“…In isolated, perfused rat lungs, PAF stimulated the synthesis and release of peptidoleukotrienes, and diethylcarbamazine, a 5-lipoxygenase inhibitor, blocked PAF-induced lung edema (22,34). Various 5-lipoxygenase inhibitors or leukotriene receptor antagonists have also been shown to inhibit PAF-induced bronchoconstriction (4), bronchial hyperreactivity (35,36), and lethality (37), suggesting that many of the pulmonary and systematic effects of PAF are leukotriene-mediated.…”
Section: Discussionmentioning
confidence: 98%
“…The baseline R L was 182.6 ± 4.8 cmH 2 O/(l/s). Values are means ± SEM (n = 6 for each group) Values are means ± SEM Statistical significance was determined by Mann-Whitney U-test a P<0.01 compared with sensititzed but unchallenged guinea-pigs tized guinea pigs (Mazzoni et al 1985;Anderson and Fennesy 1988;Sanjar et al 1990). The mechanisms for these changes may vary with the mode or dose of induction (Fitzgerald 1993).…”
Section: Discussionmentioning
confidence: 99%
“…PAF-induced pulmonary platelet accumulation was suggested responsible for this responses (Mazzoni et al 1985). In the present study, we adopted bolus injections of low dose of PAF to induce an acute, short-lived increase in reactivity which was shown to be sustained for at least 20 min in the present study, and was reported previously to subside within 30 min (Anderson and Fennesy 1988). This effect was reported to be partly dependent on lipoxygenase products and partly on a vagal reflex (Anderson and Fennesy 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation